2006
DOI: 10.1007/s10803-005-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Face Processing in Autism: Fact or Artifact?

Abstract: Within the last 10 years, there has been an upsurge of interest in face processing abilities in autism which has generated a proliferation of new empirical demonstrations employing a variety of measuring techniques. Observably atypical social behaviors early in the development of children with autism have led to the contention that autism is a condition where the processing of social information, particularly faces, is impaired. While several empirical sources of evidence lend support to this hypothesis, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(194 citation statements)
references
References 167 publications
(236 reference statements)
10
177
2
1
Order By: Relevance
“…R 2 values indicated on each graph scan paths of the eyes and mouth may be unrelated to autism diagnosis, but instead are determined (in part) by the degree of co-morbid alexithymia in the sample of individuals with autism. Second, many studies have demonstrated the importance of typical scan paths in recognising facial emotion (Aviezer et al 2008;Calder et al 2000;Smith et al 2005;Wong et al 2005), therefore if alexithymia is associated with atypical scan paths to eyes and mouth, then the inconsistent findings with respect to recognition of emotional facial expression in autism (see Bal et al 2010;Jemel et al 2006) may also be explained by varying degrees of co-morbid alexithymia in the sample of individuals with autism across studies. We suggest therefore, that future studies of emotion processing in individuals with autism obtain measures of alexithymia in order to determine whether any impairments seen are due to autism, alexithymia, or the combination of these two factors.…”
Section: Discussionmentioning
confidence: 99%
“…R 2 values indicated on each graph scan paths of the eyes and mouth may be unrelated to autism diagnosis, but instead are determined (in part) by the degree of co-morbid alexithymia in the sample of individuals with autism. Second, many studies have demonstrated the importance of typical scan paths in recognising facial emotion (Aviezer et al 2008;Calder et al 2000;Smith et al 2005;Wong et al 2005), therefore if alexithymia is associated with atypical scan paths to eyes and mouth, then the inconsistent findings with respect to recognition of emotional facial expression in autism (see Bal et al 2010;Jemel et al 2006) may also be explained by varying degrees of co-morbid alexithymia in the sample of individuals with autism across studies. We suggest therefore, that future studies of emotion processing in individuals with autism obtain measures of alexithymia in order to determine whether any impairments seen are due to autism, alexithymia, or the combination of these two factors.…”
Section: Discussionmentioning
confidence: 99%
“…While the response time increased linearly with increasing male voice manipulation in the controls, the response time curve of HFA group resembled a parabola, possibly indicating that different higher-level processes were used to perform the perceptual task. The involvement of different higher level processes during the performance of social perceptual tasks in autism has been reported, mostly related to directing attention to socially relevant clues (Dawson et al 1998;Pierce et al 1997) and analytic or piecemeal rather than holistic processing of social stimuli (Pelphrey et al 2002) (for a review see Jemel et al 2006). Thus, people with HFA may use a different, lesssocially directed, perceptual approach even though the perception of social stimuli per se is not affected.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, it is thought to result from a dysfunction of face processing neural regions such as the fusiform gyrus (Dawson et al, 2005) or amygdala (Baron-Cohen et al, 2000) and/or a lack of interest in social stimuli early in life (Dawson et al, 2005;Grelotti et al, 2002;Schultz, 2005). Parental reports and retrospective analysis of home videos indicate poor eye contact, delayed, reduced or absent gaze-following, reduced orienting to faces, lack of responsiveness to parents' voice and lack of spontaneous imitation (see Jemel et al, 2006).…”
Section: Face Processing In Asdmentioning
confidence: 99%